2021
DOI: 10.1161/circulationaha.120.053318
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of Interleukin-6 Receptor Antibodies for Modulating the Systemic Inflammatory Response After Out-of-Hospital Cardiac Arrest (The IMICA Trial)

Abstract: Background: Out-of-hospital cardiac arrest (OHCA) patients who remain comatose after initial resuscitation are at high risk of morbidity and mortality due to the ensuing post cardiac arrest syndrome (PCAS). Systemic inflammation constitutes a major component of PCAS, and interleukin-6 (IL-6) levels are associated with PCAS severity. The IL-6 receptor antagonist tocilizumab could potentially dampen inflammation in PCAS. The objective of the present trial was to determine the efficacy of tocilizumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…However, a recent study on reducing inflammation and myocardial injury after OHCA with the IL-6 receptor blocker tocilizumab, found promising effects on biomarker release, but was underpowered for detecting change in mortality [37]. Complement inhibition might also be an alternative therapeutic approach in the future [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study on reducing inflammation and myocardial injury after OHCA with the IL-6 receptor blocker tocilizumab, found promising effects on biomarker release, but was underpowered for detecting change in mortality [37]. Complement inhibition might also be an alternative therapeutic approach in the future [38].…”
Section: Discussionmentioning
confidence: 99%
“…Higher IL6 values have been reported to be associated with higher mortality, worse PCAS, and CPC of 3-5 at 12 months [11,12]. In a clinical RCT of patients with OHCA, the IL6-receptor antagonist tocilizumab decreased systemic inflammation and myocardial injury without improving the functional outcome, which was not, however, the primary endpoint [28,29]. Finally, the IL6 half-life of less than 1 h means that rapid changes in IL6 levels can be readily detected by serial assays [30].…”
Section: Discussionmentioning
confidence: 98%
“…It is worth noting that the secondary injury after ROSC is much more harmful than the primary ischemic injury [24]. Besides, systematic in ammation is crucial in the development of post-CA syndrome [25]. Several previous reports have shown that increased RDW level relates to a lot of misregulations including senescence, oxidative stress, systemic in ammation, malnutrition, and impaired kidney function [26,27].…”
Section: Discussionmentioning
confidence: 99%